1958
DOI: 10.1002/pol.1958.1203312632
|View full text |Cite
|
Sign up to set email alerts
|

The dissolution of water‐insoluble polymers in the surfactant solution. The polyelectrolyte‐like behavior of the dissolved polymers

Abstract: Polymers, such as polyvinyl formal (PVF) and polyvinyl acetate (PVAc), which are insoluble in water, dissolved in anionic surfactant solution. Polymer solutions of PVF, PVAc, and polyvinyl alcohol in surfactant were studied viscometrically and electrophoretically. The polymer forms a complex with the surfactant, the behavior of which is similar to that of polyelectrolyte. The complex is negatively charged and migrates to the anode. With dialysis of the solution of polymer‐surfactant complex against running wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1962
1962
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…Because of the association of polymers and surfactants in solution, it would not be surprising if they could influence each other's solubility, as well as that of a third component. Indeed, it has been found that SDS, for example" can actually solubilize certain normally insoluble polymers, such as polyvinylacetate" as demonstrated by Isemura and Imanishi (62). Similar work had been carried out earlier by Sata and Saito (63).…”
Section: Properties and Opportunities Relevant To Detergentsmentioning
confidence: 54%
“…Because of the association of polymers and surfactants in solution, it would not be surprising if they could influence each other's solubility, as well as that of a third component. Indeed, it has been found that SDS, for example" can actually solubilize certain normally insoluble polymers, such as polyvinylacetate" as demonstrated by Isemura and Imanishi (62). Similar work had been carried out earlier by Sata and Saito (63).…”
Section: Properties and Opportunities Relevant To Detergentsmentioning
confidence: 54%
“…These relatively large site-sizes are in fact not confined to cosolute binding by PVP, but have been observed in other polymer/ cosolute binding systems such as p01y(vinyl alcohol)/sodium dodecyl sulphate (33) and polyacrylate/aromatic quaternary ammonium compounds (34).…”
Section: Choice Of the Site-density Value Nmentioning
confidence: 94%
“…The polymer can be dissolved in a solution of surfactant, thereby creating a soluble ion complex of surfactant and organic polymer. (Isemura and Imanishi, 1958).…”
Section: Selective Polymers Based On Hydrophobic Effectmentioning
confidence: 99%